Black women in politics : demanding citizenship, challenging power, and seeking justice - Jordan-Zachery, Julia S., 1971-; Alexander-Floyd, Nikol G. (Nikol Gertrude) (SUNY series in African American studies., 2018)
This book explores how Diasporic Black women engage in politics, highlighting three dimensions--citizenship, power, and justice--that are foundational to intersectionality theory and politics as developed by Black women and other women of color. By extending beyond particular time periods, locations, and singular definitions of politics, Black Women in Politics sets itself apart in the field of women's and gender studies in three ways: by focusing on contemporary Black politics not only in the United States, but also the African Diaspora; by showcasing politics along a broad trajectory, including social movements, formal politics, public policy, media studies, and epistemology; and by including a multidisciplinary range of scholars, with a strong concentration of work by political scientists, a group whose work is often excluded or limited in edited collections. The final result expands our repertoire of methodological tools and concepts for discussing and assessing Black women's lives, the conditions under which they live, their labor, and the politics they enact to improve their circumstances.